2019
DOI: 10.4103/ijmr.ijmr_830_18
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of antimicrobial resistance of typhoidal Salmonella in India

Abstract: Background & objectives: The temporal trends in the development of antimicrobial resistance (AMR) among Salmonella Typhi and Salmonella Paratyphi in India have not been systematically reported. We aimed to systematically review the temporal AMR trends (phenotypic and molecular mechanisms) in bacterial isolates from patients with enteric fever over two decades in India. Methods: To identify trends in AMR in India, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Resistance to all three antibiotics (referred to as multidrug resistance, MDR) emerged in late 1980’s [2], predominantly due to the rise and subsequent continental migration of H58 haplotype (now referred to as 4.3.1), which contained the resistance genes either on IncH1 plasmids or integrated within the chromosome [36]. Fluoroquinolones soon became the most-commonly prescribed antibiotic [7], but since the 2000’s there have been increasing reports of decreased fluoroquinolone susceptibility due to the acquisition of chromosomal mutations in the DNA gyrase and topoisomerase IV genes [813]. In Bangladesh, >99% of all Typhi and Paratyphi A strains exhibit decreased susceptibility to ciprofloxacin [14].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to all three antibiotics (referred to as multidrug resistance, MDR) emerged in late 1980’s [2], predominantly due to the rise and subsequent continental migration of H58 haplotype (now referred to as 4.3.1), which contained the resistance genes either on IncH1 plasmids or integrated within the chromosome [36]. Fluoroquinolones soon became the most-commonly prescribed antibiotic [7], but since the 2000’s there have been increasing reports of decreased fluoroquinolone susceptibility due to the acquisition of chromosomal mutations in the DNA gyrase and topoisomerase IV genes [813]. In Bangladesh, >99% of all Typhi and Paratyphi A strains exhibit decreased susceptibility to ciprofloxacin [14].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic resistance is mainly due to selection pressure whereas extrinsic genes are acquired by horizontal transfer 21 . The recent trends in the development of antimicrobial resistance (AMR) among S. Typhi in India proposed that multidrug resistant (MDR) enteric fever was decreasing in India and being replaced by enteric fever with fluoroquinolone resistant strains 22 . Similarly, hospital-based genomic surveillance for enteric fever in Bengaluru, India using WGS method suggested that large number of isolates showed non-susceptibility to fluoroquinolones 23 .…”
mentioning
confidence: 99%
“…While the catchment area of this study is not representative of the entire Indian subcontinent, the phenomenon described herein is unlikely to be restricted to Chandigarh. India is currently the largest consumer of antimicrobials of all low- and middle-income countries, with a reported 6.5 billion defined daily doses (DDDs) in 2015, or 13.6 DDDs per 1000 inhabitants per day [ 31 , 32 ]. With such widespread availability and use of antimicrobials nationally, selective pressure on circulating pathogens is likely immense.…”
Section: Discussionmentioning
confidence: 99%